Two triphosphate tunnel metalloenzymes from apple exhibit adenylyl cyclase activity - Yuan, Ye; Liu, Zhiguo; Wang, Lili; Wang, Lixin; Chen, Shuangjiang; Niu, Yahong; Zhao, Xin; Liu, Ping; Liu, Mengjun (Frontiers in Plant Science, 2022)
Adenylyl cyclase (AC) is the key catalytic enzyme for the synthesis of 3',5'-cyclic adenosine monophosphate (cAMP). Various ACs have been identified from microorganism and mammals, while study on plant ACs is still limited, particularly no AC has been reported in woody plant by now. Based on the information of HpAC1, three enzymes were screened out from woody fruit tree apple, while two of them (MdTTM1 and MdTTM2) were verified and confirmed to display AC activity. Interestingly, in apple genome, these two genes were annotated as triphosphate tunnel metalloenzymes (TTM) which widely found in three superkingdoms of life with multiple substrate specificities and enzymatic activities, especially triphosphate hydrolase. In addition, the predicted structures of these two proteins were parallel, especially the inside of catalytic tunnel, including conserved domains, motifs and folded structure. Their tertiary structures exhibited classic TTM properties, like characteristic EXEXK motif and the β-stranded anti-parallel tunnel capable of coordinating divalent cation. Moreover, MdTTM2 and HpAC1 displaying powerful hydrolase activity to triphosphate and restricted AC activity. All these results demonstrated that MdTTMs possessed hydrolysis and AC activity which could provide a new solid proof for the distribution in woody plant of AC and insights of relationship between AC and TTM.